Teachers' Perceptions of Using Digital Gaming in Classrooms - Kokandy, Rania (International Journal of Educational Technology and Learning, 2021)
Digital gaming is a widespread activity in our society; more than 45 million homes have video-game consoles. Mostly, educators see this as a waste of valuable time that could be used for learning instead. Thus, the purpose of this qualitative study is to understand teachers' perspectives on using digital gaming among their students at Northern Illinois University in the state of Illinois. The main findings of this study discovered that most of the teachers who were interviewed have a positive attitude toward digital gaming and they think it that has a number of benefits that should not be ignored. Moreover, the results of this study revealed that teachers noted that using digital games increased students' engagement as well as improved students' skills, such as critical thinking, self- directed learning, technological skills, and self- motivation. This study has showed that indeed digital games have a bright future as a tool used at various stages of learning for different levels of students. Consequently, the educational policy makers should to embrace digital gaming as a learning tool.